2019
DOI: 10.1111/gcbb.12627
|View full text |Cite
|
Sign up to set email alerts
|

Impact of warm‐season grass management on feedstock production on marginal farmland in Central Illinois

Abstract: The production of dedicated energy crops on marginally productive cropland is projected to play an important role in reaching the US Billion Ton goal. This study aimed to evaluate warm‐season grasses for biomass production potential under different harvest timings (summer [H1], after killing frost [H2], or alternating between two [H3]) and nitrogen (N) fertilizer rates (0, 56, and 112 kg N/ha) on a wet marginal land across multiple production years. Six feedstocks were evaluated including Miscanthus x giganteu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…Improving the production of bioenergy crops, such as PCG, on the marginal lands continues to be an area of ongoing concern among the scientific community as well as the farming community worldwide (Anderson et al, 2015;Kim et al, 2012;Zumpf et al, 2019), due to the increase in food prices (Mehmood et al, 2017) and the depletion of nonrenewable fossil fuels (Pancaldi & Trindade, 2020). Providing the necessary N to the soil is essential to enable the growth of PCG as a viable biofuel on the marginal lands (Boe et al, 2009;Guo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improving the production of bioenergy crops, such as PCG, on the marginal lands continues to be an area of ongoing concern among the scientific community as well as the farming community worldwide (Anderson et al, 2015;Kim et al, 2012;Zumpf et al, 2019), due to the increase in food prices (Mehmood et al, 2017) and the depletion of nonrenewable fossil fuels (Pancaldi & Trindade, 2020). Providing the necessary N to the soil is essential to enable the growth of PCG as a viable biofuel on the marginal lands (Boe et al, 2009;Guo et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it may give farmers and other marginal landowners valuable insight into how they can manage such lands and at the same time promote soil and PCG productivity. Much research has suggested the benefits of PCG as it can decrease dependency on nonrenewable fossil fuels (Anderson et al, 2015;Zumpf et al, 2019). Improving soil and bioenergy productivity by implementing an intercropping system could be advantageous in strengthening the ecosystem, providing improved marginal land health in many regions including South Dakota (Kim et al, 2020).…”
Section: Management Implementationmentioning
confidence: 99%
“…We include temperature and precipitation including their quadratic terms and soil productivity as control variables. Our inclusion of soil productivity and N × soil productivity interaction is based on the experimental literature, which shows that the yield impact of N depends on the establishment of soil conditions (Tejera et al, 2019; Thomason et al, 2005; Zumpf et al, 2019). Since switchgrass has many cultivars and their yields differ considerably, we include genetic variability as the additional control variable.…”
Section: Empirical Strategymentioning
confidence: 99%
“…The data consists of yield observations for miscanthus planted between 2002–2017 (harvested between 2007–2019) and switchgrass planted between 2002–2013 (harvested between 2004–2018). Miscanthus data are obtained from 2 experiments in the Great Plains (Arundale, 2012; Lee et al, 2018); 11 experiments in the Midwest (Anderson‐Teixeira et al, 2013; Arundale, 2012; Arundale et al, 2014; Boersma & Heaton, 2014; Dong et al, 2019; Kaiser et al, 2015; Lee et al, 2018; Sanford et al, 2016; Tejera et al, 2019; Tejera & Heaton, 2019; Zumpf et al, 2019); 2 experiments in the Northeast (Arundale, 2012; Lee et al, 2018); and, 3 experiments in the Southeast (Arundale, 2012; Dong et al, 2019; Lee et al, 2018). Similarly, switchgrass data are obtained from 2 experiments in the Great Plains (Arundale, 2012; Lee et al, 2018); 6 experiments in the Midwest (Anderson‐Teixeira et al, 2013; Arundale, 2012; Arundale et al, 2014; Lee et al, 2018; Sanford et al, 2016; Zumpf et al, 2019); 2 experiments in the Northeast (Arundale, 2012; Lee et al, 2018); and, 3 experiments in the Southeast (Arundale, 2012; Boyer et al, 2013; Lee et al, 2018).…”
Section: Data and Statisticsmentioning
confidence: 99%
“…For example, a forage production system may include a single or two-cut harvest regime, and harvest timing (early or midseason) will be based on optimizing nutrient and crude protein concentrations to improve feed quality [34][35][36]. Under a sustainable bioenergy production system, perennial grass biomass is typically harvested once after senescence or a killing frost at the end of each growing season to allow for nutrients to translocate to belowground tissues, thereby reducing the next season's nutrient requirements and improving stand longevity [7,[37][38][39][40][41]. The differences in harvest timing and harvest frequency for these two applications can impact the crop's biomass yield and quality.…”
Section: Introductionmentioning
confidence: 99%